Maternal elevated salt consumption and the development of autism spectrum disorder in the offspring - Afroz, Kazi Farhana (J Neuroinflammation, 2019)
Autism spectrum disorder (ASD) is a prevalent neurodevelopmental condition with no known etiology or cure. Several possible contributing factors, both genetic and environmental, are being actively investigated. Amongst these, maternal immune dysregulation has been identified as potentially involved in promoting ASD in the offspring. Indeed, ASD-like behaviors have been observed in studies using the maternal immune activation mouse model. Furthermore, recent studies have shed light on maternal dietary habits and their impact on the gut microbiome as factors possibly facilitating ASD. However, most of these studies have been limited to the effects of high fat and/or high sugar. More recent data, however, have shown that elevated salt consumption has a significant effect on the immune system and gut microbiome, often resulting in gut dysbiosis and induction of pro-inflammatory pathways. Specifically, high salt alters the gut microbiome and induces the differentiation of T helper-17 cells that produce pro-inflammatory cytokines such as interleukin-17 and interleukin-23. Moreover, elevated salt can also reduce the differentiation of regulatory T cells that help maintaining a balanced immune system. While in the innate immune system, high salt can cause over activation of M1 pro-inflammatory macrophages and downregulation of M2 regulatory macrophages. These changes to the immune system are alarming because excessive consumption of salt is a documented worldwide problem. Thus, in this review, we discuss recent findings on high salt intake, gut microbiome, and immune system dysregulation while proposing a hypothesis to link maternal overconsumption of salt and children’s ASD.